2018
DOI: 10.1186/s12934-018-0861-7
|View full text |Cite
|
Sign up to set email alerts
|

Oral recombinant Lactobacillus vaccine targeting the intestinal microfold cells and dendritic cells for delivering the core neutralizing epitope of porcine epidemic diarrhea virus

Abstract: BackgroundPorcine epidemic diarrhea caused by porcine epidemic diarrhea virus (PEDV) has led to serious economic losses to the swine industry worldwide. In this study, an oral recombinant Lactobacillus casei vaccine against PEDV infection targeting the intestinal microfold (M) cells and dendritic cells (DCs) for delivering the core neutralizing epitope (COE) of PEDV spike protein was developed with M cell-targeting peptide (Col) and dendritic cell-targeting peptide (DCpep). The immunogenicity of the orally adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 43 publications
(64 reference statements)
1
62
0
1
Order By: Relevance
“…Lactobacilli are attractive vaccine candidates because they have been successfully used as hosts for bacterial and viral antigen expression and can induce immune responses by oral administration (Maassen et al 1999;Grangette et al 2001;Reveneau et al 2002;Scheppler et al 2002;Ho et al 2005;Ma et al 2018). In addition, lactobacilli have demonstrated intrinsic adjuvant activity (Perdig on et al 2001;Ogawa et al 2005;Yu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacilli are attractive vaccine candidates because they have been successfully used as hosts for bacterial and viral antigen expression and can induce immune responses by oral administration (Maassen et al 1999;Grangette et al 2001;Reveneau et al 2002;Scheppler et al 2002;Ho et al 2005;Ma et al 2018). In addition, lactobacilli have demonstrated intrinsic adjuvant activity (Perdig on et al 2001;Ogawa et al 2005;Yu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The sequences of the primers used for PCR amplification of VP60 were as follows: 5 -ATGGAGGGCAAAACCCGCACAGCGC-3 ; 5 -TCAGACATAAGAAAAGCCATTGGCT-3 . pPG-T7g10-PPT, constructed in our previous study [33], was used as a constitutive expression plasmid in this study; it encoded resistance to chloramphenicol (Cm) and contained an HCE promoter, T7g10 enhancer, PgsA anchor, and the rrnBT1T2 terminator. Plasmids pMD18-T simple-eGFP and pMD18-T simple-VP60 were constructed in our laboratory previously.…”
Section: Bacterial Strain Virus Primers and Plasmidmentioning
confidence: 99%
“…Currently, there is increasing interest in the development of L. casei oral vaccines, and this approach is significant for the effective induction of a mucosal immune response [30]. The results to date have been confirmed that the safety and the effectiveness of L. casei were used as the oral vaccine vehicle, which were extensively used in protecting individuals against a variety of pathogens [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 95%
“…PEDV strains cause porcine epidemic diarrhea (PED), characterized by vomiting, severe diarrhea, and dehydration in seronegative pigs at all ages, with high mortality in suckling pigs [3]. Many attempts have been made to develop a safe and protective vaccine for controlling PED [4][5][6][7][8][9][10]. However, similar to studies on most enterotropic and mucosal transmissible viral diseases [11][12][13][14], using intramuscular (IM) administration of inactive or subunit vaccines combined with commercial adjuvants, such as multiple emulsions of water/oil/water or a B subunit of Escherichia coli heat-labile enterotoxin (LTB) induced production of systemic IgG and neutralizing antibodies but failed to elicit a mucosal IgA response and efficient protection [6,7,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%